2009
DOI: 10.1164/rccm.200810-1552oc
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Role of Myeloid-related Protein-14 in Clinical and Experimental Sepsis

Abstract: Human sepsis and endotoxemia are associated with enhanced release of MRP8/14. In abdominal sepsis, MRP8/14 likely occurs primarily at the site of the infection, facilitating bacterial dissemination at an early phase and liver injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
100
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 56 publications
15
100
0
Order By: Relevance
“…Human pneumonia is associated with local and systemic MRP8/14 release [36,37], which correlates with findings in murine pneumonia caused by Klebsiella pneumoniae [20] or pneumococci [14,37]. In accordance, in the current model of S. aureus pneumonia, MRP8/14 levels in plasma and lungs were also increased.…”
Section: Discussionsupporting
confidence: 87%
“…Human pneumonia is associated with local and systemic MRP8/14 release [36,37], which correlates with findings in murine pneumonia caused by Klebsiella pneumoniae [20] or pneumococci [14,37]. In accordance, in the current model of S. aureus pneumonia, MRP8/14 levels in plasma and lungs were also increased.…”
Section: Discussionsupporting
confidence: 87%
“…The Mrp8/14 complex is known to be a ligand for TLR4 of which Mrp8 is the active component causing the increased expression of TNF-␣ . In patients with sepsis and in healthy humans injected with LPS, elevated Mrp8/14 plasma levels are observed [34] . Furthermore, it was shown that Mrp8/14 is released locally during severe infection in patients with peritonitis [34] .…”
Section: Myeloid-related Proteins Mrp8 and Mrp14mentioning
confidence: 99%
“…In patients with sepsis and in healthy humans injected with LPS, elevated Mrp8/14 plasma levels are observed [34] . Furthermore, it was shown that Mrp8/14 is released locally during severe infection in patients with peritonitis [34] . Investigations seeking to provide insight into the functional role of MRP8/14 revealed that Mrp14 contributes to bacterial dissemination and liver injury during abdominal sepsis [34] .…”
Section: Myeloid-related Proteins Mrp8 and Mrp14mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, MRP-14 enhances innate host-defense mechanisms. Rather, MRP-14 mice appeared to be protected from endotoxemia [35], suggesting that excessive MRP-14 concentration might be harmful, an observation that had also been made for a sudden increase of other cytokines [36].…”
Section: Mrp-14 In the Peripheral Blood Of Patients With Infection Anmentioning
confidence: 94%